Tactics Optimization of Percutaneous Coronary Intervention in the Area of Bifurcation of the Anterior Descending Artery by Means of Cardiography from the Coronary Sinus - Y.L., Shevchenko; D.Y., Ermakov; A.Y, Vakhrameeva (Cardiology and Cardiovascular Medicine, 2020)
Introduction: The aim of this investigation is to evaluate the possibilities of the method of cardiography from the coronary sinus (ECG-CS) in optimization of stenting bifurcation lesions (BL) of coronary arteries (CA). Materials and Methods: 43 patients with stable CHD with pseudo-BL of the anterior descending artery (ADA) were included in this investigation. We placed a 10-canal electrode into their coronary sinus at the beginning of percutaneous coronary intervention (PCI). Ischemic guidance was done with the WorkMate electrophysiological recording system. Results: In 11 patients (25%) out of 43 with CHD, the diagonal branch (DB) comprometation and ischemia dynamics (p<0.05) in intracardiac lead (CS 3-4) after ADA stenting were discovered according to ECG-CS. Nine patients (20.9%) underwent successful provisional-T-stenting, while a second stent was required for the other 2 patients. Conclusion: ECG-CS provides the possibility to optimize coronary intervention in the area of CA bifurcation.